Some observations in pineapple production under different fertilizer programmes and different pineapple residue management practices - Ahmed, Osumanu Haruna; Mohd Hanif, Ahmad Husni; Abd Rahim, Anuar; Musa, Mohamed Hanafi (Universiti Putra Malaysia Press, 2001)
The study evaluates the existing and potential fertilizer programmes and pineapple residue management practices in order to come out with a fertilization programme which is economically viable. The fertilizer programmes adopted were: (i) application of N (176, 176, 176, and 176 kg ha-1 ), P (11, 11, 7, and 7 kg herJ), and K (89, 89, 188, and 188 kg ha-1 ) fertilizers at 65, 135, 191, and 233 days after planting (FP1), respectively (the usual practice); (ii) application of N (176, 176, and 176 kg ha-J ) P (11, 11, and 7 kg herJ) and K (89, 89, and 188 kg ha-J) fertilizers at 65, 135, and 191 days after planting (FP2), respectively; and (iii) application of N (176,264, and 264 kg ha-1 ) P (11,14, and 11 kg ha-1 ) and K (89,183, and 285 kg ha-J) fertilizers at 65, 135, and 191 days after planting (FP3), respectively. Pineapple residue management practices used were: (i) in situ decomposition of pineapple residue without any interference (RMl); (ii) stacking of pineapple residue (leaves, crowns, and peduncles) slashed, and raked from 0.6 m x 10m beds into 0.9 m x 10m beds (RM2-zero bum technique); and (iii) in situ burning of pineapple leaves, crowns, and peduncles (the usual practice) (RM3). Combinations of the residue management practices and fertilizer programmes gave the following treatments: RM1FP1, RM1FP2, RM1FP3, RM2FP1, RM2FP2, RM2FP3, RM3FP1, RM3FP2, and RM3FP3. Neither of the fertilization programmes (FP1, FP2, and FP3) nor residue management practices (RM1, RM2, and RM3)significantly improved fruit yield. FP2 emerged as the least expensive programme followed by FP3, and then FP1. The cheapest residue management practice was RM1, followed by RM2, and RM3. RM1FP2 emerged the most economic treatment combination. Zero-bum technique (RM2), in situ decomposition of pineapple residues without any interference (RM1), in situ burning of pineapple residues did not significantly improve fruit yield, but practicing RM1 in pineapple cultivation on tropical peat is economical. Application of N, P, and K fertilizers at 65, 135, and 191 days after planting (FP2) was cost effective as it was possible to save as much as USD 110.17 ha-J, and this programme was most economically viable under pineapple residue management practice RM1.